ChemInform Abstract: Electronic Excitations in Light Absorbers for Photoelectrochemical Energy Conversion: First Principles Calculations Based on Many Body Perturbation Theory. Issue 23 (16th May 2013) - Ping, Yuan; Rocca, Dario; Galli, Giulia
Abstract Review: 261 refs.